ANALISIS PRAKTIK MANAJEMEN KUALITAS TOTAL TERHADAP KINERJA OPERASIONAL RUMAH SAKIT SWASTA - Putri Mega Pratiwi; Wahyuningsih Wahyuningsih (Peneliti.net, 2023)
This study aims to determine the effect of total quality management (TQM) practices on the operational performance of private hospitals. In collecting data, this research uses a sample of medical employees who work in private hospitals. The sample used was 204 respondents. The data analysis technique uses Structural Equation Modeling (SEM) with the help of the AMOS computer program. The results of this study indicate that total quality management (TQM) practices have a positive effect on operational performance